Major depression in hospitalized Argentine general medical patients: Prevalence and risk factors - Yanzón de La Torre, Andrés (2016)
Background: Depression is not uncommon among medically hospitalized patients, though reported prevalence has varied widely, often in samples involving elderly patients with particular illnesses. Accordingly, we evaluated risk of major depression in three metropolitan general hospitals in Buenos Aires, in subjects with a range of medical disorders and ages, comparing several standard screening methods to expert clinical examinations. Methods: Consecutively hospitalized general medical patients were evaluated over a six-months. Excluded were subjects under age 18 and those unable to participate in assessments because of illness, medication, sensory or speech impairment, or lack of language fluency, or scored <25 on the Mini Mental State Examination (MMSE). Consenting participants were examined for DSM-IV-TR major depression by psychiatrists guided by MINI examinations, compared with other standard screening methods. Risk factors were assessed by preliminary bivariate analyses followed by multivariate logistic regression modeling. Results: Overall prevalence of major depression in 257 subjects was 27% by psychiatric examination. The rate was most similar (25%) with the Hospital Anxiety & Depression Scale (HADS), and much higher with the Beck Depression Inventory-II (BDI, 44%) and Patient Health Questionnaire (PHQ, 56%). Factors associated independently with depression by multivariate modeling included: Prior psychotropic-drug treatment, female sex, more children, and heavy smoking. Depression was associated most with neoplastic, urological, and infectious disorders, least with pulmonary, neurological, and hematologic conditions. Limitations: Modest numbers limited power to test for associations of depression with specific medical conditions. Conclusions: Major depression was identified in over one-quarter of Argentine, general medical inpatients, with marked differences among screening methods. Several risk factors were identified. The findings encourage assertive identification of depression in hospitalized medical patients using valid, reliable, and cost-effective means of improving their care.